Phosphorus Removal in Constructed Stormwater Wetland Mesocosms Amended with Water Treatment Residuals - Vacca, K (Water environment research : a research publication of the Water Environment Federation, 2016)
Constructed stormwater wetlands (CSWs) reduce stormwater volume and improve water quality. One quality improvement is the removal of soluble reactive phosphorus (SRP). There has been limited study on SRP fate and transport or on the mechanisms to improve SRP removal due to the difficulty in quantifying the complex, spatially heterogeneous removal processes in two-dimensional flow. The present research analyzed the ability of wetland soil (Control) and wetland soil amended with 2%, 5%, and 8% (by mass) of aluminum-based water treatment residuals (AlWTRs) to remove SRP in surface-flow vegetated CSW mesocosms. Batch adsorption experiments showed increasing SRP sorption capacity with increased AlWTR content (590-850 mg/kg soil) compared to the Control (385 mg/kg soil); however, AlWTR-amended flowing mesocosms removed only 6.0-8.8 mg/kg SRP compared to 9.3 mg/kg SRP for the Control. The lack of increased SRP removal in AlWTR-amended mesocosms was attributed to flow dynamics (only 20% of the surface outflow was quantified as subsurface flow). These results suggest the extent of infiltration versus surface flow is key to soil amendments improving SRP removal in a CSW